2016
DOI: 10.1007/s11695-016-2317-7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Bleeding and Leakage After Sleeve Gastrectomy: a Single-Center Experience

Abstract: Postoperative bleeding was defined as a drop of hemoglobin of more than 2 g associated with pallor, tachycardia, and abdominal pain and distension. Intra-abdominal fluid collections were sought by abdominal CT scan.All patients who had bleeding (as defined before) required blood transfusion; however, major bleeding that required reoperation was seen in three patients who presented not only with drops of hemoglobin and tachycardia but they were in a state of shock, and they required urgent resuscitation and reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In our study, in four cases of the Group A and, in three cases of the Group B, the source could not be revealed at the time of re-operation. In such cases is difficult to understand what it should be done in order to diminish the risk how long we do not know which is in fact the source (9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, in four cases of the Group A and, in three cases of the Group B, the source could not be revealed at the time of re-operation. In such cases is difficult to understand what it should be done in order to diminish the risk how long we do not know which is in fact the source (9).…”
Section: Discussionmentioning
confidence: 99%
“…As for the need of routinely placement of a drainage tube, this fact is also intensely debated; therefore, certain authors consider that placing these devices will not be able to provide a faster diagnostic of this complication due to the fact that the tube can be rapidly clogged with blood clots (22). Moreover, these drainage tubes are usually removed within the 24 hours while a significant number of cases develop this complication after this interval of time (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that early postoperative bleeding is associated with surgeons’ technical failure, 12 , 22 such as lack of experience in the procedure of hemostasis and vessel ligatures, and anastomotic bleeding. Abdominal arterial bleeding usually occurs in splenic artery, hepatic artery, and gastroduodenal artery, with the incidence ranging from 0.6% to 3.3%, and the main reason for hemorrhage was anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%